UPLC-QTOF/MS-based phenolic profiling of Melastomaceae, their antioxidant activity and cytotoxic effects against human breast cancer cell MDA-MB-231 - Hazrulrizawati, Hamid; Aizi Nor Mazila, Ramli; Normaiza, Z.; M. M., Yusoff (Elsevier Ltd, 2018)
Eleven compounds were identified during profiling of polyphenols by UPLC-QTOF/MS. In abundance was quercetin-3-O-α-l-arabinofuranoside in M. malabathricum ethanolic leaves extract while 6-hydroxykaempferol-3-O-glucoside was present in the leaves extract of M. decenfidum (its rare variety). TPC and TFC were significantly higher in M. decemfidum extract than M. malabathricum extract. During DPPH, FRAF and β-carotene bleaching assays, M. decemfidum extract exhibited greater antioxidant activity compared to M. malabathricum extract. Effect of M. malabathricum and M. decemfidum extracts on viability of MDA-MB-231 cell at concentrations 6.25–100 μg/mL were evaluated for 24, 48 and 72 h. After 48 and 72 h treatment, M. malabathricum and M. decemfidum leaves extracts exhibited significant activity in inhibiting MDA-MB-231 cancer cell line with M. malabathricum extract being more cytotoxic. M. malabathricum and M. imbricatum serves as potential daily dietary source of natural phenolics and to improve chemotherapeutic effectiveness.